2020
DOI: 10.3390/molecules25020341
|View full text |Cite|
|
Sign up to set email alerts
|

Casticin Induces DNA Damage and Affects DNA Repair Associated Protein Expression in Human Lung Cancer A549 Cells

Abstract: Casticin was obtained from natural plants, and it has been shown to exert biological functions; however, no report concerns the induction of DNA damage and repair in human lung cancer cells. The objective of this study was to investigate the effects and molecular mechanism of casticin on DNA damage and repair in human lung cancer A549 cells. Cell viability was determined by flow cytometric assay. The DNA damage was evaluated by 4’,6-diamidino-2-phenylindole (DAPI) staining and electrophoresis which included co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 66 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…Casticin is a flavonoid extracted from Rhizoma butensis , which has various biological effects such as anti‐tumor, anti‐inflammatory, and improvement of airway responses in asthma 12‐14 . Besides, it has remarkable effects on nuclear factor, erythroid 2‐like 2 (Nrf2), kelch‐like ECH‐associated protein 1 (Keap1), NF‐κB, and other targets of oxidative stress and inflammation 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Casticin is a flavonoid extracted from Rhizoma butensis , which has various biological effects such as anti‐tumor, anti‐inflammatory, and improvement of airway responses in asthma 12‐14 . Besides, it has remarkable effects on nuclear factor, erythroid 2‐like 2 (Nrf2), kelch‐like ECH‐associated protein 1 (Keap1), NF‐κB, and other targets of oxidative stress and inflammation 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Co-IP and MS assays revealed that ISOC1 could interact with the DNA damage repair pathway, and further investigation confirmed that overexpression of ISOC1 led to increased DNA damage sites. Dysregulation in the DNA damage repair pathway induces the accumulation of genetic alteration and facilitates carcinogenesis in lung cancer (22). RNA sequencing results showed that the main downstream signaling pathway mediated by ISOC1 was inflammationrelated pathways, including IL-17 signaling pathway, TNF signaling pathway, cytokine-cytokine receptor interaction, NF-kappa B signaling pathway, chemokine signaling pathway, and others.…”
Section: Discussionmentioning
confidence: 99%
“…HaCaT cells (3×10 6 cells/dish) were cultured onto 10-cm dishes overnight and treated with DMSO, 500 μM H 2 O 2 or pre-treated with 20 μM tetrandrine for 1 h and then treated with 500 μM H 2 O 2 for 12 h. At the end of incubation, cells were collected, total proteins were extracted, and their protein concentration was quantified by Bio-Rad protein assay kit (Hercules, CA, USA) (40)(41)(42). A defined amount of sample (30 μg) from each treatment was separated by 10% (w/v) sodium dodecyl sulfate polyacrylamide gel electrophoresis and then transferred onto polyvinylidene fluoride membranes (Millipore, Belford, MA, USA).…”
Section: Western Blotting Analysismentioning
confidence: 99%